1.3-μm InAs/GaAs quantum dots grown on Si substrates*Project supported by the National Key Research and Development Program of China (Grant No. 2018YFA0306101), the Scientific Instrument Developing Project of Chinese Academy of Sciences (Grant No. YJKYYQ20170032), and the National Natural Science Foundation of China (Grant Nos. 61790581, 61435012, and 61505196). (December 2018) - Shao 邵, Fu-Hui 福会; Zhang 张, Yi 一; Su 苏, Xiang-Bin 向斌; Xie 谢, Sheng-Wen 圣文; Shang 尚, Jin-Ming 金铭; Zhao 赵, Yun-Hao 云昊; Cai 蔡, Chen-Yuan 晨元; Che 车, Ren-Chao 仁超; Xu 徐, Ying-Qiang 应强; Ni 倪, Hai-Qiao 海桥; Niu 牛, Zhi-Chuan 智川
Abstract : We compare the effect of InGaAs/GaAs strained-layer superlattice (SLS) with that of GaAs thick buffer layer (TBL) serving as a dislocation filter layer. The InGaAs/GaAs SLS is found to be more effective than GaAs TBL in blocking the propagation of threading dislocations, which are generated at the interface between the GaAs buffer layer and the Si substrate. Through testing and analysis, we conclude that the weaker photoluminescence for quantum dots (QDs) on Si substrate is caused by the quality of capping In0.15 Ga0.85 As and upper GaAs. We also find that the periodic misfits at the interface are related to the initial stress release of GaAs islands, which guarantees that the upper layers are stress-free.